2019
DOI: 10.1111/1471-0528.15938
|View full text |Cite
|
Sign up to set email alerts
|

The high prevalence and impact of rheumatic heart disease in pregnancy in First Nations populations in a high‐income setting: a prospective cohort study

Abstract: Objective To describe the epidemiology of rheumatic heart disease (RHD) in pregnancy in Australia and New Zealand (A&NZ). Design Prospective population‐based study. Setting Hospital‐based maternity units throughout A&NZ. Population Pregnant women with RHD with a birth outcome of ≥20 weeks of gestation between January 2013 and December 2014. Methods We identified eligible women using the Australasian Maternity Outcomes Surveillance System (AMOSS). De‐identified antenatal, perinatal and postnatal data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 29 publications
3
37
3
Order By: Relevance
“…Among the women who gave birth, 10.0% suffered decompensated heart failure peripartum, all with stenosis. Valvular surgery prior to pregnancy, a favourable prognostic factor for maternal outcome, was observed in 18.5% of women, similar to that found in the AMOSS study (16%) . An audit of Aboriginal RHD patients in primary care found that 84% of priority one patients 15–24 years had surgery, reflecting that young Australian patients mostly have access to surgery once diagnosed .…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Among the women who gave birth, 10.0% suffered decompensated heart failure peripartum, all with stenosis. Valvular surgery prior to pregnancy, a favourable prognostic factor for maternal outcome, was observed in 18.5% of women, similar to that found in the AMOSS study (16%) . An audit of Aboriginal RHD patients in primary care found that 84% of priority one patients 15–24 years had surgery, reflecting that young Australian patients mostly have access to surgery once diagnosed .…”
Section: Discussionsupporting
confidence: 78%
“…In Australasia, RHD in pregnancy is rare (4.3/10 000 women giving birth) compared with that seen in low‐ and middle‐income countries . Given the tertiary setting and high‐risk condition, caesarean births in our RHD cohort (44%) were higher than those for WA and KEMH in 2014 (39% and 36% respectively) as well as higher than found in the AMOSS study (30%) which included non‐tertiary settings . Mitral stenosis was reported in approximately half the women in our study compared with 37% in the AMOSS cohort, with similar prevalence of mitral regurgitation in the two studies .…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations